Método filogenômico para inferência de árvore de espécie de organismos procariotos: uma nova abordagem filogenética para reconciliação de genes transferidos horizontalmente - Nilson Antonio da Rocha Coimbra (2019)
Classically, concatenated alignments of the small subunits of ribosomal RNA sequences (rDNA's) have been used to reconstruct bacteria phylogenies and identify new species. On the one hand and in the light of evolution, the genomic content of microorganisms is largely affected by Horizontal Gene Transfers - HGT, whereas, on the other hand, the reconstruction of microbial phylogenies using the classical sequence-based approach does not account for the presence of Horizontally transferred genes. In this work, we improve the methods of microbial phylogeny reconstruction, while accounting for the presence of HGT genes. We present a new gene tree-based method to correct putative transferred genes and applied this new method in the phylogenomic reconstruction of the Order Corynebacteriales, the largest clade in the Phylum Actinobacteria. We collected 360 genome records of Corynebacteriales from NCBI RefSeq Database, release 81 and estimate the phylogeny reconstruction using both concatenated-based (RaxML) and summary-based (ASTRAL and ASTRID) methods. Overall, all the reconstructed trees exhibited a highly resolved resolution and feasibility for the microbial classification, detecting speciation among the Corynebacterium genus.